Effectiveness of the “INTIMOTRI” treatment in strengthening motor processes in psychology students (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2022)
INTRODUCTION: The objective of this study was to evaluate participants' motor stability using the manual "Hole Test for Assessing Motor Stability" and implement the "INTIMOTRI" treatment through interventions aimed at promoting proper functioning and efficient development of the human body, coordination, and balance in students. METHOD: The method proposed in this study is quantitative and features a pre-experimental, retrospective, cross-sectional design using five interventions, each session lasting approximately thirty minutes, and targeted sampling among second-semester psychology students at the University of Santander, Cúcuta campus. RESULTS: Data collected from the initial and final assessments were analyzed and compared using SPSS. All hypotheses were null (no statistically significant difference) because the results were greater than 0.05.
Keywords: Motor stability; psychomotor skills; treatment; young adults